Leading with Purpose: Co-Constructing Leadership Identity through Role Clarity and Collaboration - Husain, Farhat N. (Human Resource and Leadership Journal, 2025)
Purpose: The Purpose of this study is to investigate how purpose-driven leadership and clearly defined responsibilities could improve leaders' performance, collaboration, and team morale. It specifically looks at how co-creating a common "Why" statement and mapping responsibilities into a three-tiered framework (core, extended, and professional) minimises job ambiguity, empowers teams, and aligns leadership practices with organisational goals. Methodology: The study used a qualitative case study design and a sixty-minute professional learning session with Subject Leaders from an international secondary school. The workshop used Role Theory (Biddle, 1979), Role Leadership Theory (Katz & Kahn, 1966), and Servant Leadership (Greenleaf, 2002) to incorporate structured reflection, collaborative discourse, and consensus building. Findings: Co-creating a "Why" statement improved clarity, morale, and psychological safety. By mapping roles into the Tiered Framework, leaders were able to remove ambiguity, empower teams, and promote institutional alignment. Although the session was designed for Subject Leaders at one international school, the method may be used to a variety of contexts, including healthcare, business, and non-profit sectors, where role clarity and common purpose are critical. Contribution to Theory, Policy and Practice: The study combines Role Theory, Role Leadership Theory, and Servant Leadership with Simon Sinek's (2011) concept of "Start with Why," to provide a practical paradigm that connects role clarity with purpose-driven leadership. By incorporating these frameworks into the Tiered Responsibility model, it demonstrates how structured reflection and collective meaning-making may support leadership growth in complex organisations.